Primary architecture and energy requirements of Type III and Type IV secretion systems - Cabezón, Elena; Valenzuela-Gómez, Fernando; Arechaga, Ignacio (Frontiers in Cellular and Infection Microbiology, 2023)
Many pathogens use Type III and Type IV protein secretion systems to secrete virulence factors from the bacterial cytosol into host cells. These systems operate through a one-step mechanism. The secreted substrates (protein or nucleo-protein complexes in the case of Type IV conjugative systems) are guided to the base of the secretion channel, where they are directly delivered into the host cell in an ATP-dependent unfolded state. Despite the numerous disparities between these secretion systems, here we have focused on the structural and functional similarities between both systems. In particular, on the structural similarity shared by one of the main ATPases (EscN and VirD4 in Type III and Type IV secretion systems, respectively). Interestingly, these ATPases also exhibit a structural resemblance to F1-ATPases, which suggests a common mechanism for substrate secretion. The correlation between structure and function of essential components in both systems can provide significant insights into the molecular mechanisms involved. This approach is of great interest in the pursuit of identifying inhibitors that can effectively target these systems.